4-Aminoquinoline: a comprehensive review of synthetic strategies - Delgado, Francisco; Benítez, Andrés; Gotopo, Lourdes; Romero, Angel H. (Frontiers in Chemistry, 2025)
4-Aminoquinoline is an important scaffold due to its variety of applications in medicinal, synthetic organic, and industrial chemistry. It has gained great relevance for the development of selective and potent leishmanicidal agents targeting parasite mitochondria, agonists and antagonists of Toll-like receptors (TLRs), antimalarials, and anticancer agents. As a consequence of the importance of 4-aminoquinoline as leishmanicidal, the present mini-review article aims to give comprehensive information about the different synthetic alternatives for the synthesis of 4-aminoquinolines, including (i) reactions based on nucleophilic aromatic substitution via conventional heating, microwave, and ultrasound; (ii) one-pot metal-free or metal-catalyzed reactions of inter- and intramolecular cyclization/annulation; (iii) miscellaneous reactions including the dehydrogenative amination of dihydroquinolin-4(1H)one and amination via Hartwig–Buchwald cross-coupling or rearrangement reactions.